Impact of cyclosporine A-related single nucleotide polymorphisms on post-transplant outcomes in pediatric hematologic malignancy patients undergoing allogeneic hematopoietic stem cell transplantation - Ji, Qi; Zhang, Senlin; Liu, Minyuan; Zhang, Weiliang; Liu, Lixia; Chai, Yutan; Gao, Li; Li, Bohan; Du, Zhizhuo; Hu, Yixin; Xiao, Peifang; Ling, Jing; et al. (Frontiers in Immunology, 2025)
BackgroundCalcineurin inhibitors (CNIs), such as cyclosporine A (CsA), are widely used as immunosuppressants for both prophylactic and therapeutic purposes in patients with graft-versus-host disease (GVHD) after allogeneic hematopoietic stem cell transplantation (allo-HSCT). CsA-related transporters and metabolic enzymes single nucleotide polymorphisms (SNPs) are associated with the efficacy of CsA in individuals. However, few studies have explored how CsA-related SNPs correlate with post-transplant complications and prognosis.MethodsHere, our study involved 128 pediatric hematological malignancy patients undergoing allo-HSCT with GVHD prophylaxis based on CsA. All patients were detected for CsA-related SNPs. We investigated the associations between the CsA-related SNPs and post-transplant complications and prognosis.ResultsWe examined twenty-three CsA-related SNPs. Based on multivariate analysis using Cox regression, we identified umbilical cord blood HSCT and donor-recipient HLA matches of 9/10-10/10 as independent factors for peri-engraftment syndrome (hazard ratio (HR) = 2.82, P = 0.008; HR = 0.30, P = 0.021, respectively); recipient weight ≤ 26 kg, donor-recipient major or minor ABO blood type mismatch, and CYP2C19 (99T>C) variant genotype as independent risk factors for grades II-IV acute GVHD (aGVHD) (HR = 2.08, P = 0.008; HR = 2.56, P = 0.008; HR = 2.22, P = 0.014; HR = 1.80, P = 0.042, respectively); matched unrelated donor HSCT and donor-recipient HLA matches of 9/10-10/10 as independent factors for Epstein-Barr virus infection (HR = 5.22, P = 0.019; HR = 0.13, P = 0.003); CYP3A5 (219-237C>T) variant genotype as an independent protective factor for cytomegalovirus infection (HR = 0.58, P = 0.025); recipient being male, age at transplantation ≤ 104 months, ABCB1 (1236C>T) CT/TT genotype, and SLCO1B1 (1865 + 4846T>C) TC/CC genotype as independent factors for hemorrhagic cystitis (HR = 2.65, P = 0.024; HR = 0.46, P = 0.023; HR = 0.39, P = 0.030; HR = 0.32, P = 0.001, respectively); and donor-recipient HLA matches of 9/10-10/10 as an independent protective factor for capillary leak syndrome (CLS) (HR = 0.19, P = 0.031). Additionally, we found a body weight ≤ 26 kg, CLS after HSCT, SLC29A1 (-162 + 228A>C) AC/CC genotype were independent factors for both disease-free survival (HR = 0.38, P = 0.022; HR = 2.64, P = 0.023; HR = 0.29, P = 0.016, respectively) and overall survival (HR = 0.27, P = 0.007; HR = 3.83, P = 0.003; HR = 0.22, P = 0.005, respectively).ConclusionOur study revealed correlations between CsA-related transporters and metabolic enzymes SNPs and post-transplant complications and prognosis, contributing to a better understanding of the interindividual difference in efficacy. Future studies on adjusting the dosage of drugs based on SNPs in clinical practice may be one of the options for improving the HSCT outcomes.